The Enforceability of the Decision of the Construction Dispute Board in Indonesia - Haliman, Yudi; Adolf, Huala; Fakhriah, Efa Laela; Murwadji, Tarsisius (Badan Arbitrase Nasional Indonesia, 2025)
The emergence of the Dispute Board in Indonesia through Law Number 2 of 2017 on Construction Services raises several challenges, including the complexity of the dispute resolution process, the unclear legal status of decisions, and the lack of recognition within the existing arbitration legal framework. Using a legal normative approach, this research explores the issue in the dispute resolution mechanism under the Law Number 2 of 2017, analyses the main obstacles, and formulates recommendations for improving the effectiveness of the Dispute Board. This research in particular emphasized the enforceability of the decision of the Construction Dispute Board. The method to this problems was to analyze the provisions under the Law. In addition this article also analyzed the main provision on the settlement of disputes, including the possibility of the legal recognition of the Dispute Construction Board in view of the institutional aspects under the Law No 30 of 1999 on Arbitration and Alternative Dispute Resolution. This article found that the complexity of the dispute resolution process through the Construction Dispute Board, along with the high cost and lack of clarity regarding the enforceability of judgments, creates uncertainty for the parties. This marred the deicison of the Construction Dispute Board.